(untitled) (Cadernos de Sociomuseologia, 2015)
Over time many have developed conceptions of museums, the old cabinets of curiosity to the public museums emerged in the post-French Revolution, designed to build national identity and ’enlighten the masses’. However, the emergence of a new design museum asan institution built by the community participation and for social change is recent, the second half of the twentieth century. This article aims to present the context of pregnancy and the development of the New Museology. For that, it starts showing the evolution ofmuseums until the Second World War. Then, presenting the advances entities within which arise the new design: UNESCO, ICOM and ICOMOS. And, finally, focuses on MINOM and developing their new ideas through their forums and resolutions, providing anoverview of them. Keywords: MINOM; ICOM; ICOMOS; Museums; New Museology